THE EFFECT OF USING CARROT LEAF FLOUR (Daucus carrota) IN RATIONS ON COMMERCIAL CARCASS PIECES IN MALE BALI DUCKS - I K. W. A., Ariasa; Wibawa, A.A.P. P.; Puspani, E. (Jurnal Peternakan Tropika, 2024)
This study aims to determine the effect of using carrot leaf flour in rations on commercial carcass pieces in male bali ducks. The research was carried out for 42 days at Jalan Tegal Wangi II Gang Kavling No. 9 Sesetan, Denpasar, Bali. The design used was a completely randomized design (CRD) consisting of 4 treatments and 6 replications. Each experimental plot was filled with 4 male bali ducks aged 2 weeks with a body weight of 181,19 ± 9,06 g per head. The four treatments were male bali ducks that were given a ration without carrot leaf flour as a control (A), a ration with 3% carrot leaf flour (B), a ration with 6% carrot leaf flour (C), and a ration with 9% carrot leaf flour (D). The observed variables is cutting weight, carcass percentage, thigh percentage, and chest percentage. Statistically, the use of carrot leaf flour in the ration had a significant effect on commercial carcass pieces in male bali ducks (P<0,05). The cutting weight in treatments A, B, C and D was 692,17g; 723,83g; 883g; and 762g; respectively. The percentage of carcasses in treatments A, B, C and D were 58,25%; 61,59%; 61,61%; and 61,44%; respectively. The percentage of thighs in treatments A, B, C and D were 29,38%; 29,75%; 29,8%; and 29,72%; respectively. The percentage of the chest in treatments A, B, C and D were 20,36%; 21,97%; 22,2%; and 21,79%; respectively. The conclusion from the results of this study was that the use of carrot leaf flour (Daucus carota) in the ration could increase the carcass fraction of male Bali ducks.